Sustainability in higher education institutions: analysis of academic publication linked to management - Barbosa , Abigail Alves de Sousa; Cabral, Lílian Caporlíngua Giesta; Nobre, Fábio Chaves; Perlin, Ana Paula (Revista de Administração da UFSM, 2024)
Purpose: To analyze and discuss how the topic of sustainability is addressed in higher education institutions (HEIs) in publications linked to the area of management. Design/approach/methodology: To meet the proposed objective, a bibliometric review was developed based on a qualitative analysis in order to investigate implicit or explicit references to the way sustainability is discussed in academia. Results: It appears that, although the importance of HEIs in the formation of a sustainable social mentality is well established in theoretical and practical debate, their role portrayed in studies still seems modest and diffuse. Research limitations/implications: The main limitation of this study refers to the restriction of the results found, as they are based on a selection and the delimitations and methodological choices of the research found in the bibliometric review. Originality/value: In addition to the relevance of the theme, this study allows a panoramic view of how sustainability is being approached in higher education institutions, as these are important agents that form and guide sustainable development in society. The study also has practical value, as the inferences found can support and direct managers’ decision-making in favor of the inclusion of sustainability in academia.